Sonochemical reduction of Cr(VI) in air in the presence of organic additives: What are the involved mechanistic pathways? - Meichtry, Jorge Martin (2018)
The sonochemical (850 kHz) reduction of Cr(VI) (0.3 mM, pH 2, reactor open to air) was analyzed in the presence of different additives. The effects on Cr(VI) reduction efficiency of added formic acid (FA, 10 mM), citric acid (Cit, 2 mM), ethylenediaminetetraacetic acid (EDTA, 1 mM), methanol (MeOH, 0.1 M), ethanol (EtOH, 0.1 M), 2-propanol (2-PrOH, 0.1 M), tert-butanol (t-BuOH, 0.1 M), phenol (PhOH, 2 mM) and sodium lauryl sulfate (SLS, 1 mM) have been evaluated in comparison with the system in the absence of additives. Complete Cr(VI) reduction was obtained only when using EDTA (at 120 min) and Cit (at 180 min). Cr(III) complexes with these compounds or with their degradation products were detected as final products. For EDTA, Cit, t-BuOH, FA and SLS, the Cr(VI) decay could be adjusted to a zero-order kinetics; in the cases of MeOH, EtOH and 2-PrOH, there was a deviation from the zero-order kinetics. The Cr(VI) conversion increased in the order SLS (very low) < no additive ≅ MeOH ≅ EtOH ≅ 2-PrOH < FA < t-BuOH < PhOH < Cit < EDTA. The role of EDTA and Cit in stabilizing intermediate Cr(V) peroxo compounds and enhancing their direct transformation into different Cr(III) species is considered a major factor in the acceleration of Cr(VI) reduction processes. Mechanistic pathways are proposed.